Report of a Rare Case of Gorham-Stout Disease of Both Shoulders: Bisphosphonate Treatment and Shoulder Replacement - Eike Garbers; Falk Reuther; Gunther Delling (Case Reports in Rheumatology)
Massive osteolysis known as Gorham-Stout disease is a rare idiopathic disorder typically affecting long bones in a unifocal pattern. Angiomatosis is strongly connected to the osteolysis. Weather angiomatosis is the cause or the result of osteolysis is subject of intense discussion (Kawasaki et al. (2003), Möller et al. (1999), Radhakrishnan and Rockson (2008)). There are about 200 cases described since 1955. Our patient is a 77-year-old female patient with osteolyses of both shoulders involving the proximal humerus, lateral clavicle, and the glenoid. Under bisphosphonate therapy, the progressive osteolysis stopped on the right side and showed progression on the left. With the patient complaining about severe rest pain and impaired function, we performed surgical reconstruction by implantation of total shoulder prosthesis three months after onset of symptoms. Our case shows a possibility of primary and early surgical reconstruction with good clinical outcome.